ARTIFICIAL MATURATION STUDY OF COAL FROM GUNUNG MAS, KALIMANTAN TENGAH DAN MUARO JAMBI, JAMBI BASED ON VARIATION OF TEMPERATUR AND TIME - NURUDDIN AKBAR (NIM : 12113014), HARUN
A lot of information about Indonesian coal are still not well understood, especially in detailed stages during coalification. The stages are controlled by temperature, pressure, and time. Those three factors mutually affect toward the maturity of the coal. The maturity of coal or usually referred as rank can be determined by analysis of some parameters such as the calorific value and proximate analysis. The proximate analysis consists of inherent moisture, fixed carbon, and volatile matter contents. The samples being studied were collected from Tumbangjutuh, Rungan, Gunung Mas, Kalimantan Tengah and Muaro Jambi, Jambi. Geologically, the samples from Gunung Mas, Kalimantan Tengah is part of Miocene Warukin formation. Meanwhile the samples from Muaro Jambi, Jambi is part of Miocene Muaraenim formation. The rank of Gunung Mas coal is subbituminous B with composition of IM 16,18%; Ash 12,07%, Carbon 31,59%, volatile matter 40,16% and the calorific value 4.777 kkal/kg (adb). Whereas the coal from Muaro Jambi, Jambi exhibits rank of subbituminous B with composition of IM 15,97(%), Ash 2,84(%), Carbon 37,19(%), volatile matter 44,00(%) and the calorific value 5.196 kkal/kg (adb). The temperature variations used in the artificial maturation are 750C, 1000C, 1250C, 1500C, 1750C, 2000C, 2250C, and 2500C, running for 24-hours. The time variatons used in the artificial maturation are 3, 6, 12, 18, 24 hours, running at temperature of 2500C. Heating process with the temperature and time variations on both samples is able to show changes to proximate analysis and calorific value which indicate the maturation of coal. Both variations that used in this study could increase the rank of both sample from subbituminous B to subbituminous A by ASTM D388-99 coal classification.